Factors Influencing Customer Satisfaction or Dissatisfaction in the Restaurant Business Using AnswerTree Methodology - Hwang, Jinsoo; Zhao, Jinlin (My University, 2010)
In the restaurant business, customer satisfaction can be linked directly to restaurant sales; thus, it is important to identify which perceived quality factors more strongly affect customer satisfaction or dissatisfaction. The purpose of this study was to find differences between satisfied and dissatisfied customers. The major analytical method used was AnswerTree. As AnswerTree method allows the researcher to more effectively target exact groups of people, it is a suitable analysis method to find differences between satisfied and dissatisfied customer groups. Study results indicated three perceived quality factors (good value, tasty food, and restaurant cleanness) most affected satisfied customers. On the other hand, three perceived quality factors (good value, tasty food, and employees’ knowledge of menu) most affected dissatisfied customers. Study results provide some meaningful information for restaurateurs in making a marketing strategy.
Keywords: Customer satisfaction; Perceived quality; AnswerTree; CHAID